South Pole penguins - Lumry, Amanda; Hurwitz, Laura (Bellevue, WA : Eaglemont Press, 2007)
Riley accompanies Uncle Max, Aunt Martha, and Cousin Alice to Antarctica, the coldest place on earth, to investigate the diet of the penguins there to see whether it has changed because of rising ocean temperatures.
Ages 4-8.
Keywords: Penguins -- Fiction; Antarctica -- Fiction